Expert assessment of the dual form of training of railroad workers in an educational and industrial complex - Bakatanova, V. B.; Baglay, V. I. (Problems of Engineer-Pedagogical Education, 2019)
Conducting theoretical and pilot studies on the introduction of dual vocational training (dual form of vocational training) of railroad workers needs quantitative and qualitative evaluation of results. The method of expert evaluation helps quantitatively estimate the subjects of the research study according to certain characteristics, order and classify them. Realization of this method to assess the dual form of training of railroad workers in the educational-industrial practice complex demanded the implementation of a certain number of actions such as: 1) to outline the main objectives of the research study and to develop its program; 2) to design a questionnaire used to carry out expert evaluation; 3) to conduct a survey of experts; 4) to consider factors which might distort the results of expert evaluation; 5) to estimate the representativeness of an expert group; 6) to process the results of expert evaluation; 7) to carry out an analysis and interpretation of the results obtained through the survey. To account of possible mistakes when processing the questionnaires received from the experts, two filters were introduced: 1) competence filter; 2) subjectivity filter (extrema). The data obtained through the survey of experts represent sets of the estimates of relative importance, put by the expert on each subject under consideration. On the basis of the data obtained from experts positive conclusions were drawn on appropriateness of using the dual form of education in the process of vocational training of future railroad workers.